Research advances in roles of microRNAs in nasal polyp - Zhipu, Niu; Zitao, Huo; Jichao, Sha; Cuida, Meng (Frontiers in Genetics, 2022)
MicroRNAs (miRNAs), a subset of endogenous RNAs highly conservative with short chains, play key regulatory role in the biological relevant events of the cells. Exosomes are extracellular vesicles like the plasma membrane components being able to deliver information molecules such as miRNA between cells and to regulate the fate of the target cells. The progression of chronic rhinosinusitis with nasal polyps (CRSwNP) is closely associated with significant alterations of miRNA levels in both cells and exosomes. RNA-binding proteins (RBPs) have been acknowledged to play important roles in intracellular miRNA transport to exosomes, and specific membrane proteins such as caveolin-1 critically involved in HNRNPA1 -mediated transport of miRNA to exosomes. Aberrant alteration in endogenous miRNA levels significantly contributes to the process of airway remodeling in the nasal tissue and to the occurrence and progression of inflammatory responses in CRSwNP. Exogenous miRNAs delivered via exosomes has also been shown to play an important role in activating macrophages or in regulating vascular permeability in the CRSwNP.This paper highlights the mechanism of RBP-mediated delivery of miRNAs to exosomes and the important contribution of endogenous miRNAs to the development of CRSwNP in response to inflammation and airway remodeling. Finally, we discuss the future research directions for regulation of the miRNAs to CRSwNP.Delivery of exogenous miRNAs by exosomes alters the endogenous miRNAs content in nasal mucosal epithelial cells or in associated inflammatory cells in the CRSwNP, and altered endogenous miRNAs affects the inflammatory response and airway remodeling, which then regulates the occurrence and progression of CRSwNP.RBPs and associated membrane proteins such as caveolin-1 may play a crucial role in the entry of exogenous miRNA into exosomes.